Uang Panai in Bugis Wedding Traditions - Marwing, Anita; Susanto (Hikmatuna : Journal for Integrative Islamic Studies, 2024)
This study analyses the implementation of Bugis community marriage in Malangke in accordance with the maqashid al-syariah. This study uses qualitative research with primary data from traditional, religious, and community leaders. The implementation of Bugis community marriage through cultural Islamization so as not to conflict with Sharia. In culture, there are benefits for both the wife and husband. This kind of marriage culture is called al-adah al-sahihah or al-urf al-sahih, namely good customs and can be used as legal considerations. In community marriage, there is a Mappasikarawa or mappasiluka (first contact) section, following the hadith of the Prophet Muhammad SAW, who gave instructions to husbands when they were about to marry a woman, they should hold her crown, read the basmalah, pray for blessings and read. In addition, Mappassau Botting and Cemme Passili (caring for and bathing the bride) are in accordance with the principle of maqasid al-syariah of descent (Nasl). The dowry in maqashid al-syariah is classified as maslahat tahsiniyyat, a benefit based on beautifying relationships. The tradition of giving dowry can be justified according to Islamic law as a form of upholding the value of family honour. Maqashid al-syariah and marriage of the Bugis community to realize goodness while avoiding evil or bringing benefits (maslahah).